2005
DOI: 10.1002/ps.1028
|View full text |Cite
|
Sign up to set email alerts
|

Toxic and repellent effects of Baccharis salicifolia essential oil on Tribolium castaneum

Abstract: Allelochemical effects were observed when Tribolium castaneum (Herbst) adults were treated with Baccharis salicifolia (Ruiz & Pavon) Pers essential oil. The main biological activities were toxicity and repellence. Terpenes present in the essential oil were identified by GC-MS, and some authentic samples were tested to assess their activity individually. The most acutely toxic compounds after 3 days were beta-pinene and pulegone. Most of the monoterpenes elicited symptoms indicative of neurotoxicity. The most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(108 citation statements)
references
References 32 publications
6
89
1
4
Order By: Relevance
“…The insecticidal constituents of many plant essential oils are monoterpenoids. The insecticidal activity of monoterpenes has also been reported against stored products insects (Ho et al, 1997;Garcìa et al, 2005). The insecticidal activity of the essential oils investigated in the present study may be attributed to their major constituents of monoterpenes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The insecticidal constituents of many plant essential oils are monoterpenoids. The insecticidal activity of monoterpenes has also been reported against stored products insects (Ho et al, 1997;Garcìa et al, 2005). The insecticidal activity of the essential oils investigated in the present study may be attributed to their major constituents of monoterpenes.…”
Section: Discussionsupporting
confidence: 73%
“…Essential oils and extracts of some aromatic plants purchased from South Korean markets revealed contact and fumigant toxicities toward S. oryzae (Kim et al, 2003). Garcìa et al (2005) reported that essential oil of Baccharis saliciflia (Asteraceae) had toxic and repellent effects against T. castaneum.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids are known to influence herbivorous insects in various ways: they can be part of direct defenses as repellents, feeding deterrents or toxins, with the toxicity of terpenoids possibly due to neurotoxic effects (Garcia et al, 2005;reviewed by Gershenzon andCroteau, 1991 andLangenheim, 1994). Terpenoids can also be used as attractants and/or feeding or oviposition stimulants by specialist herbivores; they can be part of indirect defense as attractants for carnivores; and they can be part of sexual reproduction and outcrossing as attractants of pollinators (Gershenzon and Croteau, 1991;Langenheim, 1994).…”
Section: Plant-insect Interactionsmentioning
confidence: 99%
“…The red flour beetle Tribolium castaneum Herbst Coleoptera: Tenebrionidae is worldwidely distributed and among the most economically important stored product pests 2 . Infestations can also result in elevated temperature and moisture conditions that lead to an accelerated growth of molds, including toxigenic species 3 .…”
Section: Introductionmentioning
confidence: 99%